\(a,x^3=216\)
=>\(x^3=6^3\)
=>x=6
Các câu sau như thế
\(x^3=216\Rightarrow x=\sqrt[3]{216}=6\)
\(3x^2=x^2\)
\(\Rightarrow3x^2-x^2=0\)
\(\Rightarrow x^2\left(3-1\right)=0\)
\(\Rightarrow x^2=0\Rightarrow x=0\)
\(x^5=x^4\)
\(\Rightarrow x^5-x^4=0\)
\(\Rightarrow x^4\left(x-1\right)=0\)
\(\Rightarrow\left[{}\begin{matrix}x^4=0\\x-1=0\end{matrix}\right.\)
\(\Rightarrow\left[{}\begin{matrix}x=0\\x=1\end{matrix}\right.\)
Bổ sung tiếp :
b ) \(3x^2=x^2\)
\(\Leftrightarrow3x^2-x^2=0\)
\(\Leftrightarrow2x^2=0\)
\(\Rightarrow x=0\)
Vậy \(x=0\)
c ) \(x^5=x^4\)
\(\Leftrightarrow x^5-x^4=0\)
\(\Leftrightarrow x^4\left(x-1\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x^4=0\\x-1=0\end{matrix}\right.\Rightarrow\left[{}\begin{matrix}x=0\\x=1\end{matrix}\right.\)
Vậy \(x=0\) và \(x=1\)